Social support and prosocial behavior in Chinese college students during the COVID-19 outbreak: a moderated mediation model of positive affect and parental care - Huang, Ziyang; Gan, Quan; Luo, Miaoling; Zhang, Yunpeng; Ge, Jie; Fu, Yu; Chen, Zhuangfei (Frontiers in Psychology, 2023)
Purpose: Prosocial behaviour (PSB) plays a critical role in everyday society, especially during the pandemic of COVID-19. Understanding the underlying mechanism will provide insight and advance its implementation. According to the theory of PSB, social interaction, family and individual characters all contribute to its development. The current study aimed to investigate the influencing factor of PSB among Chinese college students during COVID-19 outbreak. This is an attempt to understand the mechanism of PSB and to provide a reference for the formulation of policies aimed at promoting healthy collaborative relationships for college students. Method: The online questionnaire was administered to 664 college students from 29 provinces of China via Credamo platform. There were 332 medical students and 332 non-medical students aged between 18-25 included for final study. The mediating role of positive emotion/affect (PA) and the moderating role of parental care in the association between social support and PSB during the pandemic of COVID-19 was explored by using Social Support Rate Scale (SSRS), Prosocial Tendencies Measurement Scale (PTM), The Positive and Negative Affect (PANAS), as well as Parental Bonding Instrument (PBI). The process macro model of SPSS was adopted for mediating and moderating analysis. Results: The results showed that social support positively predicted PSB among Chinese college students, even after adding PA as a mediation variable. PA during COVID-19 mediated the association between social support and PSB. PSB also revealed as a predictor of PA by regression analysis. Moreover, the moderating effect of parental care in the relationship between PA and PSB was detected. Conclusion: PA under stress acts as a mediator between social support and PSB. This mediating effect was moderated by PC in childhood. In addition, PSB was observed to predict PA reversely. The promoting factors and path between the variables of PSB are complex and need to be explored extensively. The underlying factors and process should be further investigated for the development of intervention plans.